No Fate But What We Make: a Case of Full Recovery After Out-of-Hospital Cardiac Arrest - Miranda, M (2012)
An 80 years old man suffered a cardiac arrest shortly after arrival to his local health department. Basic Life Support was started promptly and nine minutes later, on evaluation by an Advanced Life Support team, the victim was defibrillated with a 200J shock. When orotracheal intubation was attempted, masseter muscle contraction was noticed: on reevaluation, the victim had pulse and spontaneous breathing.Thirty minutes later, the patient had been transferred to an emergency department. As he complained of chest pain, the ECG showed a ST segment depression in leads V4 to V6 and laboratory tests showed cardiac troponine I slightly elevated. A coronary angiography was performed urgently: significant left main plus three vessel coronary artery disease was disclosed.Eighteen hours after the cardiac arrest, a quadruple coronary artery bypass grafting operation was undertaken. During surgery, a fresh thrombus was removed from the middle left anterior descendent artery. Post-operative course was uneventful and the patient was discharged seven days after the procedure. Twenty four months later, he remains asymptomatic.In this case, the immediate call for the Advanced Life Support team, prompt basic life support and the successful defibrillation, altogether, contributed for the full recovery. Furthermore, the swiftness in the detection and treatment of the acute reversible cause (myocardial ischemia in this case) was crucial for long-term prognosis.